Analytical and numerical modeling for the assessment of CO2 storage in the Parinas geological formation - Talara, Peru - Pomar-Castromonte, Rafu (2021)
This project was funded by the Consejo Nacional de Ciencia, Tec-nologia e Innovacion Tecnologica (CONCYTEC) of the Peruvian gov-ernment within the framework of the 159-2017-FONDECYT Agreement. The authors would like to thank Perupetro for providing valuable information used in this work.